Intel microprocessors - Brey, Barry B. (Pearson, 2014)
[This book] provides a comprehensive view of programming and interfacing of the Intel family of Microprocessors from the 8088 through the latest Pentium 4 and Core2 microprocessors. The text is written for students who need to learn about the programming and interfacing of Intel microprocessors, which have gained wide and at times exclusive application in many areas of electronics, communications, and control systems, particularly in desktop computer systems. A major new feature of this eighth edition is an explanation of how to interface C/C++ using Visual C++ Express (a free download from Microsoft) with assembly language for both the older DOS and the Windows environments. Many applications include Visual C++ as a basis for learning assembly language using the inline assembler. Updated sections that detail new events in the fields of microprocessors and microprocessor interfacing have been added. Organized in an orderly and manageable format, this text offers more than 200 programming examples using the Microsoft Macro Assembler program and provides a thorough description of each of the Intel family members, memory systems, and various I/O systems.